Red Cell Alloimmunization in Repeatedly Transfused Cancer Patients - Shahida Mohsin, Sameen Amjad, Huma Amin, Tahir Saeed; ShabbirHussain (Journal of Rawalpindi Medical College, 2013)
Background: To determine the frequency and specificities of red blood cells -antibodies in multi-transfused cancer patients. Methods: From total of 150 patients, 24 patients were diagnosed with haematological and 126 with non-haematological malignancies. Their medical records were reviewed and sorted by diagnosis, treatment medications, and past transfusion and/or treatment history. Only those patients were enrolled who had received at least five transfusions during the treatment. Antibody screening was performed by using commercial three-cell panel according to standardized methods. Allo-antibody was identified by using 11 cells panel. Results: Total patients with malignant disorders included 44 males and 106 females. Nine patients (6%) with non haematological malignancies possessed RBC allo-antibodies. The distribution of different allo-antibodies in positive patients was anti-D in 3 patients, anti-E in 2 patients while anti- Fya, anti Fyb, anti-Jka and anti-K were positive for 1 patient in each. The presence of allo-antibodies was statistically significant in patients with higher number of transfusions (p-value 0.001). Conclusion: Allo-antibodies against Rh system were most frequent. Incidence of RBCs allo-immunization increases with the number of transfusion and the number of donor exposures to the recipient.